FROM HIGH SCHOOL TO THE UNIVERSITY. TAKING THE FIRST STEP ON A CAREER PATH - Mihaela DIACONU; Olimpia OANCEA; Victoria-Mihaela BRÎNZEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
The question received at least once by any child is: ”What do you want to be when you grow up?” Translated into academic language, the question refers to the career you dream at and involves a path to get there. For today's young people, choosing the right career is a real milestone. With the ultimate goal in mind, you start making certain choices to gain, develop and improve certain skills. The first step towards the dream career is the choice of the university and, implicitly, of the study program that will allow you to develop the necessary skills, a choice that is influenced by many factors. This paper aims to identify the main factors that can influence the choice of a career path and to analyze how young people perceive the importance of education in choosing a career.